Parceltrace : Development of parcel management web application for melati college staff - Zulkafali, Maryam Jamilah
Nowadays, technology is growing rapidly that need the manual system to be converted to the web-based application system. This project describes about ParcelTrace Management Web Application, which is web-based application system platform. This system focuses on the distribution of the parcel. This system was developed purposely to help the staffs of Melati College who have problem in distributing the parcel and keeping track of all records regarding the parcel distribution. Currently, the management of the college distribute the parcel in manual ways. This project will implement two main features which are the parcel management system and real-time SMS notification to improve the management of the Melati College. This application also provides real-time SMS notification that can notify the residents of Melati College about the arriving parcel. The objectives of this project are to identify the user requirements of ParcelTrace Management Web Application, to design as well as to develop the ParcelTrace Management Web Application. In order to develop this project, the methodology used in this project is Web Development Life Cycle (WDLC), which is consist of planning, analysis, design and development, testing and finally, implementation and maintenance phases. As the result, ParcelTrace Management Web Application helps the staffs to distribute the parcel, provide parcel management system, and delivery real-time SMS notification to the residents. Some recommendations for future works are also discussed at the end of the project based on the limitation identified throughout the project to offer opportunities for enhancement and improvement for the future.